Penerapan Strategi Reap (Read, Encode, Annote, Ponder) untuk Meningkatkan Kemampuan Mengolah Informasi Siswa dalam Pembelajaran Sejarah - Aisyah Aisyah; Erlina Wiyanarti (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2021)
The background of this research was motivated by the findings of researchers in Class XI Unggulan A SMA Pasundan 8 Bandung which showed the lack of ability process student information in historical learning, when the students found information but they have not been able to develop it into renewable information and only move the information without process and the students just memorizing or reading some information when they communicating information to othe stuents. The ability to process information emphasized in this research is managing informations from historical texts and other sources, both finding information, concluding, and communicating informations, classroom action research method which is carried out with four cycles from planning, observation, action, and reflection, the method was designed by Kemmis and Mc. Taggart. Based on research that has been carried out in three cycles student have progress in achieving the criteria in the indicator of ability to process information by showing a good and significant increase in each cycles. By using REAP strategy to improve the ability to process information and use history text as a source of information for student. They can get used to managing the information, found so that the REAP strategy is one way that can be used to improve the ability to process information in history learning. The result of this study can be used as consideration for teacher to implement it, so thatstudent have the ability to process information.